Proceedings of the 3rd International Workshop on Sharing and Reusing Architectural Knowledge 2008
DOI: 10.1145/1370062.1370078
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging analysis-aided design decision knowledge in UML-based development of embedded systems

Abstract: Many important works have been carried out to provide modeling languages (e.g., UML, SDL) with expressiveness to support embedded system design, validation and verification. A fundamental shortcoming in current model-driven approaches is the inability to explicitly capture design decisions and trade-offs between different non-functional parameters, among which timeliness, memory usage, and power consumption are of primary interest. This paper highlights technical limitations in UML to specify complex non-funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Other works focused on large scale architecture optimization, decision and trade-off analysis [28][29] [30] [31]. In the automotive domain, a multi-objective automatic optimization approach based on EAST-ADL modeling is proposed [28].…”
Section: B Architecture Optimization Decision and Trade-off Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Other works focused on large scale architecture optimization, decision and trade-off analysis [28][29] [30] [31]. In the automotive domain, a multi-objective automatic optimization approach based on EAST-ADL modeling is proposed [28].…”
Section: B Architecture Optimization Decision and Trade-off Analysismentioning
confidence: 99%
“…A similar work in [29] presented a method for the search of optimal architecture design according to multi-objectives such as cost, performance and reliability based on SysML modeling. In [30], the authors identified limitations in UML language to support architecture decision according to non-functional attributes. They propose a framework based on parametric analysis specification that aims at evaluating design decisions.…”
Section: B Architecture Optimization Decision and Trade-off Analysismentioning
confidence: 99%
“…Additional tool support was created ) to help the developer to adapt to guidelines of the SAV. Espinoza et al (2008) described how to use design decisions based on analysis results and showed the limitations of the UML concerning these aspects. There are also methodical steps identified, how the developer can make such a design decision.…”
Section: Introductionmentioning
confidence: 99%